Polymer nano net film and application thereof in oil product water removal

The preparation of polymer nanomembranes through emulsion electrospraying technology has solved the problems of poor continuity, uneven mesh distribution and complex preparation process of existing nanomembrane materials in oil product water removal, and achieved efficient oil product water removal and separation efficiency and simplified preparation process.

CN119607625AActive Publication Date: 2025-03-14JIANGNAN UNIV
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411791378.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing nanomesh materials have poor continuity, uneven mesh distribution, insufficient functionality and complex preparation process in oil removal, which limit their practical application.

Method used

By controlling the particle size of the emulsion by using solvent polarity differences and ultrasonic waves, an emulsion electrospraying technology is used to form a polymer nanometer membrane with a uniform pore structure, achieving the characteristics of two-dimensional nanometer continuous, high coverage and uniform mesh holes.

Benefits of technology

The separation efficiency of emulsified water in oil products has been significantly improved, reaching more than 98%, and the preparation process has been simplified, reducing production costs and technical thresholds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119607625A_ABST
    Figure CN119607625A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer nano net film and application thereof in water removal of oil products, and belongs to the technical field of nano net films. According to the polymer nano net film material, the particle size of emulsion is controlled through ultrasonic waves by means of the polarity difference of solvents, a fiber network with a uniform pore structure is formed through polymer emulsion electronic injection, the polymer nano net film material has the advantages that a two-dimensional nano net is continuous, the coverage rate is high, and net holes are uniform, and the obtained nano net film has the high separation efficiency (gt; 98%). In addition, the technology does not depend on external complex conditions applied during electronic injection, and the preparation process is simple and controllable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano-membrane, and in particular relates to a polymer nano-membrane and its application in dewatering oil products. Background Art

[0002] In the production, distribution and storage of fuel, the mixing of water is a common phenomenon (called emulsified water). This mixing may not only lead to incomplete combustion of fuel, affect combustion efficiency, increase carbon smoke and particulate matter emissions, and aggravate air pollution, but also generate corrosive compounds, thereby accelerating the corrosion of engines, fuel systems, pumps and pipelines; and even clog injectors due to the growth of microorganisms, thereby interfering with engine operation. Emulsified water poses a challenge in the field of fuel purification due to its tiny particle size and difficult precipitation characteristics.

[0003] At present, the removal of emulsified water in fuel mainly relies on the filter in the engine fuel supply system, and its key component is fuel filter paper. This filter paper needs to have fine pores to effectively intercept emulsified water and good chemical stability to ensure long-term use, and exhibit hydrophobic and oleophilic properties. However, the existing fuel filter material is mainly melt-blown non-woven fabric / paper-based composite filter material, which has a coarse fiber diameter (>2μm), and thus has the disadvantage of large pore size, resulting in low separation efficiency of emulsified water (separation efficiency <92%).

[0004] In order to refine the fiber diameter and improve the emulsified water separation efficiency, ZL202210663134.6 discloses a fluffy nano-filter material and its preparation method and application, which is specifically obtained by hot pressing and compounding an electrospun nanofiber layer and a non-woven fabric. However, the diameter of traditional electrospun nanofibers is relatively coarse (>100nm), resulting in a large pore size of the separation membrane (>2μm), making it difficult to achieve effective separation of emulsified water. CN103806221A discloses a method for preparing a multi-component mesh nanofiber membrane, which enhances the tip instability of the Taylor cone by introducing nanoparticles, further promotes the formation of tiny charged droplets, and obtains a two-dimensional nano-net / nanofiber composite material (fiber diameter in the net <50nm). However, the resulting nano-net is randomly interspersed and distributed in the traditional electrospun fiber membrane, so that there are large gaps between the nets, which easily leads to leakage of emulsified water droplets and is difficult to be applied to the separation of emulsified water in fuel. CN107476132A discloses a method for preparing a stacked spider web composite filter paper, using hydrophobic paper coated with nanofibers as the substrate, and using ultrasonic pre-atomization technology to prepare a stacked spider web composite filter paper with micro-nano gradient pores. The average diameter of the fiber in the net is 20-100nm, which is an order of magnitude lower than that of ordinary electrostatic fibers. However, since the preparation relies on ultrasonic pre-atomization and electric field secondary atomization technology, the size of the tiny charged droplets is uncontrollable and the droplet movement is uncertain, resulting in poor continuity of the nanonet, uneven mesh distribution, and low coverage. In addition, the technology also involves complex equipment and multi-step operations, including a composite process of bidirectional electric field drafting and spraying non-woven fabrics, which increases production costs and technical barriers, is not easy to simplify, and limits its service life in harsh industrial environments.

[0005] Although the above-mentioned prior art has prepared nano-mesh materials and reduced the diameter of fibers in the mesh, it still has defects such as poor nano-mesh continuity, uneven mesh distribution, insufficient functionality, and complex preparation process, which seriously limit the practical application of the material.

[0006] Therefore, there is an urgent need to develop polymer nanomesh materials for oil water removal with good inter-mesh continuity, uniform mesh distribution and simple preparation process. Summary of the invention

[0007] [Technical issues]

[0008] The nanomesh materials prepared by the existing technology still have defects such as poor nanomesh continuity, uneven mesh distribution, insufficient functionality, and complex preparation process, which seriously limit the practical application of the material in oil water removal.

[0009] [Technical solution]

[0010] In order to solve the above technical problems, the purpose of the present invention is to provide a polymer nano-membrane and its application in oil dewatering. The polymer nano-membrane material utilizes the difference in solvent polarity, controls the emulsion particle size through ultrasound, and forms a fiber network with a uniform pore structure through polymer emulsion electrospraying. It has the advantages of continuous two-dimensional nano-mesh, high coverage, and uniform mesh. The obtained nano-membrane has high separation efficiency (>98%) for emulsified water in oil products. In addition, the invention does not rely on the complex external conditions applied during electrospraying, and the preparation process is simple and controllable.

[0011] In order to achieve the above purpose, the technical solutions provided are as follows:

[0012] A method for preparing a polymer nanomembrane, the method comprising the following steps:

[0013] (1) dissolving a hydrophobic and lipophilic polymer in a polar solvent A to obtain a solution B;

[0014] (2) ultrasonically dispersing the solution B obtained in step (1) in a non-polar solvent C to obtain a spunlace solution; wherein the solution B and the solvent C are immiscible;

[0015] (3) The spunlace solution obtained in step (2) is subjected to electrostatic spunlace to obtain a polymer nanomembrane.

[0016] In one embodiment, the hydrophobic and oleophilic polymer in step (1) is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polystyrene, polyvinyl chloride, polyetherimide, polychlorotrifluoroethylene, polysulfone, polycaprolactone, polymethyl methacrylate, polyvinyl pyrrolidone, and polyethylene terephthalate, or a mixture of any two or three of the above polymers.

[0017] In one embodiment, the molecular weight of the polyvinylidene fluoride is 300,000 to 800,000; the molecular weight of polyvinylidene fluoride-hexafluoropropylene is 300,000 to 700,000; the molecular weight of polystyrene is 150,000 to 700,000; the molecular weight of polyvinyl chloride is 20,000 to 99,000; the molecular weight of polyetherimide is 20,000 to 80,000; the molecular weight of polytrifluorochloroethylene is 100,000 to 200,000; the molecular weight of polysulfone is 35,000 to 80,000; the molecular weight of polycaprolactone is 36,000 to 100,000; the molecular weight of polymethyl methacrylate is 15,000 to 120,000; the molecular weight of polyvinyl pyrrolidone is 300,000 to 1,300,000; and the molecular weight of polyethylene terephthalate is 20,000 to 50,000.

[0018] In one embodiment, in the solution B of step (1), the mass fraction of the polymer is 5-20%.

[0019] In one embodiment, the polar solvent A in step (1) is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, acetone, dimethyl sulfoxide, ethanol, methanol, chloroform, dichloromethane, trifluoroacetic acid, ethylene glycol, tetrahydrofuran, methyl pyrrolidone, and dimethylformamide.

[0020] In one embodiment, the ultrasonic dispersion in step (2) has a power of 500 to 2500 W.

[0021] In one embodiment, the particle size of solution B in the spunlace solution of step (2) is 10 to 100 nm.

[0022] In one embodiment, the non-polar solvent C in step (2) is one or more of trichloroethane, carbon tetrachloride, carbon tetrafluoride, n-hexane, cyclohexane, isobutane, n-butane, methylcyclohexane, heptane, n-dodecane, n-tetradecane, hexadecane, and petroleum ether.

[0023] In one embodiment, the mass ratio of solution B to solvent C in step (2) is 1:99 to 20:80.

[0024] In one embodiment, the parameters of the electrostatic spraying described in step (3) are: temperature 10-30°C, relative humidity 20%-70%, infusion speed 0.1-30mL / h, voltage 5-60kV, distance between the receiving device and the spinneret 10-30cm, slide distance 0-10cm, the receiving device is a metal roller, the temperature of the receiving device is 10-50°C, and the rotation speed of the receiving device is 20-100n / min.

[0025] The present invention also provides a polymer nano-membrane prepared by the above-mentioned preparation method.

[0026] The invention also provides application of the polymer nano-membrane in removing water from oil products.

[0027] In one embodiment, the application places the polymer nanomembrane in a dead-end filtration device to remove water from oil.

[0028] The present invention also provides a method for improving the efficiency of water removal and separation in oil products, wherein the method uses the above-mentioned polymer nano-membrane as a filter membrane to remove water.

[0029] Beneficial effects:

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention utilizes ultrasonic dispersion of a polymer / polar solvent solution in a non-polar solvent to achieve the formation of tiny droplets of the polymer / polar solvent solution, and then utilizes the deformation and phase separation of these tiny droplets in an electric field to obtain a nano-membrane with a continuous two-dimensional network structure.

[0032] 2. The present invention adopts emulsion electrospraying technology to realize the preparation of polymer nano-mesh, and the steps are simple, flexible and easy to operate. Compared with the prior art, this method has the advantages of high coverage of two-dimensional nano-mesh, good structural stability and strong controllability.

[0033] 3. The polymer nanomembrane prepared by the present invention not only has the fine two-dimensional mesh structure unique to nanomembrane, but also has continuous mesh surfaces and uniform mesh sizes, which can significantly improve the oil removal performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The SEM images of the polymer nanomembranes of Examples 1-4 of the present invention; (a) is Example 1; (b) is Example 2; (c) is Example 3; (d) is Example 4;

[0035] Figure 2 The SEM images of the products prepared in Comparative Examples 1-3 are as follows; (a) is Comparative Example 1; (b) is Comparative Example 2; and (c) is Comparative Example 3. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. The following specific implementation methods further describe the present invention.

[0037] The test method involved in the present invention is:

[0038] 1. Appearance

[0039] The morphology of the fiber membrane samples was characterized by scanning electron microscopy (SEM, SU-8010, Hitachi, Japan).

[0040] 2. Separation performance

[0041] Preparation of water-in-oil emulsion: Mix water and oil in a volume ratio of 1:99, and prepare the water-in-oil emulsion by ultrasonication at a power of 400 W for 30 minutes. The oil can be diesel, gasoline, kerosene, or motor oil. The particle size of the emulsified water in the obtained water-in-oil emulsion is less than 1 μm.

[0042] The membrane was placed in a dead-end filtration device to conduct an emulsion separation experiment, and the water content (W) of the emulsion and the filtrate was tested. The separation efficiency (%) of the membrane was calculated according to formula (1):

[0043]

[0044] Example 1

[0045] A method for preparing a polymer nanomembrane comprises the following steps:

[0046] (1) adding polyvinylidene fluoride with a molecular weight of 570,000 to an N,N-dimethylformamide solvent, wherein the mass percentage of the polyvinylidene fluoride is 16 wt %, and fully dissolving the polyvinylidene fluoride to prepare a uniform solution A;

[0047] (2) adding solution A to n-hexane solvent, wherein the mass ratio of solution A to n-hexane is 1:9, and ultrasonicating with an ultrasonic machine with a power of 1200 W until solution A is completely emulsified and the particle size is 10 to 90 nm, thereby obtaining a spunlace emulsion;

[0048] (3) Under the conditions of humidity of 35% and ambient temperature of 30°C, the spunlace emulsion was added to an electrospinning device, and electrospinning was carried out under the conditions of static voltage of 20 kV, injection pump flow rate of 0.5 mL / h, and fiber receiving distance of 10 cm to obtain a polyvinylidene fluoride nanomesh, wherein the fiber diameter in the mesh was about 8 to 67 nm.

[0049] Example 2

[0050] A method for preparing a polymer nanomembrane comprises the following steps:

[0051] (1) adding polystyrene with a molecular weight of 400,000 to N,N-dimethylformamide to dissolve the polystyrene in a mass percentage of 14 wt %, so that the polystyrene is fully dissolved to prepare a uniform solution A;

[0052] (2) adding solution A to hexadecane solvent, wherein the mass ratio of solution A to hexadecane is 1:9, and ultrasonicating with an ultrasonic machine with a power of 1000 W until solution A is completely emulsified and the particle size is 20 to 100 nm, thereby obtaining a spunlace emulsion;

[0053] (3) Under the conditions of a humidity of 45% and an ambient temperature of 25°C, the spunlace emulsion was added to an electrospinning device, and electrospinning was performed under the conditions of an electrostatic voltage of 30 kV, a syringe pump flow rate of 1 mL / h, and a fiber receiving distance of 15 cm to obtain a polystyrene nanomesh, wherein the fiber diameter in the mesh was about 10 to 97 nm.

[0054] Example 3

[0055] A method for preparing a polymer nanomembrane comprises the following steps:

[0056] (1) adding polyetherimide with a molecular weight of 38,000 to dimethyl sulfoxide to dissolve the polyetherimide, wherein the mass percentage of the polyetherimide is 12 wt %, and fully dissolving the polyetherimide to prepare a uniform solution A;

[0057] (2) adding solution A to petroleum ether solvent, wherein the mass ratio of solution A to petroleum ether is 1:8, and ultrasonicating with an ultrasonic machine with a power of 1000 W until solution A is completely emulsified and the particle size is 10 to 100 nm, thereby obtaining a spunlace emulsion;

[0058] (3) Under the conditions of a humidity of 50% and an ambient temperature of 23°C, the spunlace emulsion was added to an electrospinning device, and electrospinning was performed under the conditions of an electrostatic voltage of 25 kV, a syringe pump flow rate of 1.5 mL / h, and a fiber receiving distance of 20 cm to obtain a polyetherimide nanomesh membrane, wherein the fiber diameter in the mesh was about 10 to 48 nm.

[0059] Example 4

[0060] A method for preparing a polymer nanomembrane comprises the following steps:

[0061] (1) adding polymethyl methacrylate with a molecular weight of 35,000 to N,N-dimethylformamide to dissolve the polymethyl methacrylate in an amount of 18 wt % to fully dissolve the polymethyl methacrylate to prepare a uniform solution A;

[0062] (2) adding solution A to cyclohexane solvent, wherein the mass ratio of solution A to cyclohexane is 1:8, and ultrasonicating with an ultrasonic machine with a power of 800 W until solution A is completely emulsified and the particle size is 10 to 100 nm, thereby obtaining a spunlace emulsion;

[0063] (3) Under the conditions of a humidity of 40% and an ambient temperature of 25°C, the spunlace emulsion was added to an electrospinning device, and electrospinning was performed under the conditions of an electrostatic voltage of 20 kV, a syringe pump flow rate of 1 mL / h, and a fiber receiving distance of 25 cm to obtain a polymethyl methacrylate nanomesh, wherein the fiber diameter in the mesh was about 8 to 81 nm.

[0064] Comparative Example 1

[0065] The only difference from Example 1 is that step (2) is omitted and solution A is directly used as the spinning solution for electrospinning. The rest is consistent with Example 1.

[0066] The SEM image of the product prepared in this comparative example is as follows Figure 2 As shown in a.

[0067] Depend on Figure 2It can be seen that compared with Example 1, the final sample obtained in Comparative Example 1 contains only nanofibers but no two-dimensional nanonet. This is mainly because the spinning jet of the high-concentration polymer solution is difficult to overcome the surface tension in the electric field and atomize into droplets, resulting in difficulty in forming polymer droplets and thus difficulty in forming a nanonet film.

[0068] Comparative Example 2

[0069] The only difference from Example 1 is that step (2) only involves physical stirring without ultrasonic dispersion, and the obtained particle size is 5 to 8 mm. The rest is the same as Example 1.

[0070] The SEM image of the product prepared in this comparative example is as follows Figure 2 As shown in b.

[0071] Depend on Figure 2 b It can be seen that: compared with Example 1, the sample finally obtained in Comparative Example 2 only has nanofibers, and no nanomesh is formed. This is mainly because the polymer droplets cannot be dispersed into nanosize under physical stirring alone, and larger droplets are difficult to overcome surface tension in the electric field to form a nanomesh.

[0072] Comparative Example 3

[0073] (1) adding polyvinylidene fluoride to N,N-dimethylformamide solvent, wherein the mass percentage of the polyvinylidene fluoride is 16 wt %, so that it is fully dissolved to prepare a uniform solution A;

[0074] (2) adding solution A into acetone solvent, wherein the mass ratio of solution A to acetone is 1:9, to obtain a spinning solution;

[0075] (3) Under the conditions of humidity of 35% and ambient temperature of 30°C, the spinning solution was added to the electrospinning device, and electrospinning was performed under the conditions of static voltage of 20 kV, injection pump flow rate of 0.5 mL / h, and fiber receiving distance of 10 cm.

[0076] Depend on Figure 2 c It can be seen that compared with Example 1, the final sample obtained in Comparative Example 3 only has microspheres but no two-dimensional nanonet. This is because N,N-dimethylformamide and acetone are both polar solvents with good compatibility, resulting in no formation of tiny droplets in the spinning solution, making it difficult to form a nanonet membrane.

[0077] Performance Testing

[0078] Oil dewatering performance test:

[0079] Preparation of water-in-oil emulsion: Mix oil and water in a volume ratio of 99:1, and prepare water-in-oil emulsion at a power of 560 W for 30 minutes. The oil can be diesel, gasoline, kerosene, or motor oil. The particle size of the emulsified oil in the obtained water-in-oil emulsion is less than 1 μm.

[0080] The membrane materials prepared in the examples and comparative examples were placed in a dead-end filtration device for separation experiments. The water content in the emulsion and the filtrate was tested using a coulometric Karl Fischer moisture meter, and the separation efficiency (%) of the membrane was calculated. The experimental results are shown in Table 1 below:

[0081] Table 1. Separation efficiency of membranes prepared in Examples and Comparative Examples (%)

[0082]

[0083]

[0084] In summary, the emulsion spraying technology of the present invention successfully realizes the preparation of nano-mesh membranes. The method has simple steps and flexible operation. The prepared material not only has structural characteristics such as high two-dimensional nano-mesh coverage, small mesh pore size, and large membrane porosity, but also shows high separation efficiency and high oil flux in the application field of oil water removal.

[0085] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing a polymer nanomembrane, characterized in that: The preparation method comprises the following steps: (1) dissolving a hydrophobic and lipophilic polymer in a polar solvent A to obtain a solution B; (2) ultrasonically dispersing the solution B obtained in step (1) in a non-polar solvent C to obtain a spunlace solution; wherein the solution B and the solvent C are immiscible; (3) The spunlace solution obtained in step (2) is subjected to electrostatic spunlace to obtain a polymer nanomembrane.

2. The preparation method according to claim 1, characterized in that: The hydrophobic and oleophilic polymer in step (1) is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polystyrene, polyvinyl chloride, polyetherimide, polychlorotrifluoroethylene, polysulfone, polycaprolactone, polymethyl methacrylate, polyvinyl pyrrolidone, and polyethylene terephthalate, or a mixture of any two or three of the above polymers.

3. The preparation method according to claim 1, characterized in that: The polar solvent A in step (1) is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, acetone, dimethyl sulfoxide, ethanol, methanol, chloroform, dichloromethane, trifluoroacetic acid, ethylene glycol, tetrahydrofuran, methyl pyrrolidone and dimethylformamide.

4. The preparation method according to claim 1, characterized in that: The particle size of solution B in the spunlace solution of step (2) is 10 to 100 nm.

5. The preparation method according to claim 1, characterized in that: The non-polar solvent C in step (2) is one or more of trichloroethane, carbon tetrachloride, carbon tetrafluoride, n-hexane, cyclohexane, isobutane, n-butane, methylcyclohexane, heptane, n-dodecane, n-tetradecane, hexadecane and petroleum ether.

6. The preparation method according to claim 1, characterized in that: The parameters of the electrostatic spraying described in step (3) are: temperature 10-30°C, relative humidity 20%-70%, infusion speed 0.1-30mL / h, voltage 5-60kV, distance between the receiving device and the spinneret 10-30cm, slide distance 0-10cm, the receiving device is a metal roller, the temperature of the receiving device is 10-50°C, and the rotation speed of the receiving device is 20-100n / min.

7. The polymer nanomembrane prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the polymer nanomembrane according to claim 7 in removing water from oil products.

9. The use according to claim 8, characterized in that: The polymer nano-membrane is placed in a dead-end filtration device to remove water from the oil.

10. A method for improving the water removal and separation efficiency in oil products, characterized in that: The method comprises using the polymer nanomembrane described in claim 8 as a filter membrane to remove water.

Citation Information

Patent Citations

  • Biodegradable oil-water separation net film with super-hydrophobic and super-oleophylic properties and preparation method thereof.

    CN103157392A

  • Oil and water separating mesh film and preparing method and application thereof

    CN104998552A

  • Composite film capable of adjusting liquid one-way permeation range and preparation method thereof

    CN105664730A

  • High-throughput efficient 2D net-shaped ultrafine nanofiber oil-water separation material and preparation method thereof

    CN107557894A

  • Nano gold tube composite film coated with graphene oxide and preparation method thereof

    CN110819942A